CARVEDILOL AS A POTENTIAL ADDITION TO THE COVID-19 THERAPEUTIC ARSENAL - MD., NAKHLE AYOUB (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
No single therapeutic agent has been recognized so far as the ultimate treatment for COVID-19 and many treatment strategies rely on associating different medications with proven or hypothetical anti-viral effects. Carvedilol is a third-generation beta-blocker displaying potential inhibitory properties on several key enzymatic processes and pathways involved in SARS-CoV-2 or other coronaviruses replication, in addition to the modulatory effect on several inflammatory messengers of COVID-19. These data could provide a reasonable hypothetical background for further investigating specific anti-SARS-CoV-2 effects and could pave the way for further clinical verification.